ON RATIONAL COMBINATION OF RADIOMETRIC AND LITHO-GEOCHEMICAL METHODS OF URANIUM DEPOSITS EXPLORATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
According to the results of haloes lithogeochemical studies of Pkhrut hydrothermal uranium deposit, is established that the application of phase chemical analysis (the detection of content of mobile uranium in samples) allows to determine secondary haloes of uranium deposits, which in sizes significantly exceed haloes delineated by radiometric method. It is established that the combined use of these two methods significantly increases the reliability of uranium mineralization prospecting (especially blind one).
Keywords: lithogeochemical haloes; Pkhrut hydrothermal uranium deposit; secondary haloes of uranium deposits; uranium mineralization